Metastatic malignancy masquerading as neurocysticercosis. (2019) - DiMarco, Daniela E.; Hale, Andrew J.; Ulano, Adam; Smith, Lindsay M.
Abstract: Cystic brain lesions are a common clinical dilemma facing infectious disease providers. A broad differential diagnosis is required in the proper evaluation and care of patients facing such an illness. Here the authors describe the case of a 29-year-old woman who presented with seizures and was found to have multiple cystic brain lesions, with risk factors for neurocysticercosis. Ultimately, she was found to have a metastatic neuroendocrine malignancy. The authors review the ideal imaging and testing modalities in the diagnosis and exclusion of neurocysticercosis. This case serves as guidance for clinicians caring for patients with cystic brain lesions that may be infectious or non-infectious in etiology.